A influência de grupos de interesse na definição da política cicloviária da cidade de São Paulo (2013 - 2019) - Matos, Caio Victor Aloe da Silva (2021)
This project deals with the issue of Participation and Influence of Interest Groups in the Bicycle’s Public Policy of São Paulo, during the period 2013-2019. This issue is relevant, because during the period studied, there were criticisms of the development and implementation of the project during the administration of Mayor Fernando Haddad (PT), which extended during the administration of Mayors João Doria (PSDB) and Bruno Covas (PSDB). In this way, to avoid the wastage of public policy and ensure that the process is transparent, inclusive, communicative and that it can contemplate the most different interests, criteria to determine the Effectiveness of Participation in Public Policies can be part of the solution to this and other problems. The main objective of this project was to identify and analyze the criteria that can be used to evaluate the effectiveness of methods of participation, applied in the process of building a cycle’s policy in the city of São Paulo, allowing the government to be successful in implementing this type of public policy, through a Single Case Study of the entity Ciclocidade, data collection techniques were used through interviews, primary data and direct observation for data collection. Through the analysis of the data, it can be seen that the Public Policy Defense through the Advocacy of the Ciclocidade entity was important for the cycling policy of São Paulo. From the comparison of data obtained from the three sub-units, it was possible to develop nine prepositions and find two new factors that identify participation assumptions that are Feeling and Understanding about public policy, which can be used to assess the effectiveness of participation in the construction of public policies, in addition to identifying the types of participatory advocacy techniques adopted by Ciclocidade.